ADVANCING PEDIATRIC HERNIA SURGERY: A COMPARATIVE STUDY OF OPEN AND LAPAROSCOPIC REPAIR. : J Peop Univ Med Health Sci. 2025:15(2), 91-99. http://doi.org/10.46536/jpumhs/2025/15.02.628 - Naseem Mengal1, Ali Raza Brohi2, Aiman Ali Brohi3, Ali Faraz Brohi4, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
BACKGROUND: Pediatric inguinal hernia repair is a common surgical procedure, with open herniotomy being the traditional approach in resource-limited settings. However, the introduction of laparoscopic techniques has shown promising outcomes. OBJECTIVE: This study evaluates and compares the outcomes of open and laparoscopic hernia repairs in pediatric patients at Peoples University of Medical and Health Sciences (PUMHS) Nawabshah. METHODS: A retrospective cohort study was conducted, including 300 pediatric patients (aged 1 month to 14 years) who underwent hernia repairs between January 2020 and December 2024. Patient demographics, surgical techniques, operative duration, post-operative complications, and recurrence rates were collected. Statistical analysis was performed using chi-square and t-tests to identify significant differences between the two approaches. RESULTS: Open herniotomy was performed in 76.7% of cases, while 23.3% underwent laparoscopic repair. The mean operative time for open surgery was 47 minutes, significantly longer than 38 minutes for laparoscopic repair (p < 0.05). Post-operative complications were higher in open repairs (30%) compared to laparoscopic repairs (7%) (p < 0.05). Recurrence rates were also higher in the open group (6%) versus the laparoscopic group (3%). Laparoscopic repairs demonstrated superior outcomes in terms of fewer complications, shorter operative times, and reduced recurrence. CONCLUSION: Laparoscopic hernia repair offers significant advantages over open surgery in pediatric patients, including shorter operative times, lower complication rates, and fewer recurrences. Given these benefits, investment in laparoscopic training and infrastructure in resource-limited settings like PUMHS Nawabshah is recommended to improve surgical outcomes and patient satisfaction.